2009
DOI: 10.4067/s0716-10182009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Infección rinosinusal por Scedosporium apiospermum en un hospedero inmunocompetente

Abstract: Scedosporium apiospermum rhinosinusal infection in an immunocompetent hostScedosporium species can cause colonization, superficial and deep localized infection or systemic disease, especially in immunocompromised hosts. We report a case of localized infection due to Scedosporium apiospermum in a 47 year old woman, with previous nasal surgery. She consulted for recurrent mucopurulent post-nasal discharge not responding to antibiotics. Computed tomography showed opacification of right maxillary sinus. Surgery wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Most of these cases have involved patients who are immunocompromised, and thus, relatively more vulnerable to infection by opportunistic pathogens. But, some cases have involved patients who are immunocompetent (Chanqueo et al, 2009). Indeed, species of the opportunistic fungi Scedosporium have become increasingly recognized as an emerging pathogen among the ever-increasing population of immunocompromised individuals.…”
Section: Fungimentioning
confidence: 99%
“…Most of these cases have involved patients who are immunocompromised, and thus, relatively more vulnerable to infection by opportunistic pathogens. But, some cases have involved patients who are immunocompetent (Chanqueo et al, 2009). Indeed, species of the opportunistic fungi Scedosporium have become increasingly recognized as an emerging pathogen among the ever-increasing population of immunocompromised individuals.…”
Section: Fungimentioning
confidence: 99%
“…The immune status of the patient plays an important role in the development of this fungal disease, immunocompromised patients mainly showing aggressive infections; by contrast, immunocompetent individuals tend to present benign disease, manifested as colonizations or fungal balls (Chanqueo et al, 2009). Unfortunately, one of the limitations of the present study was that the information related to the immune status of patients in the database provided was limited and, in some cases, absent.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have reported that 10-13% of patients suffering CRS are infected by fungi and 13-28% had the maxillary sinus compromised (Chanqueo et al, 2009), equivalent to 80% of cases of FRS (Chanqueo et al, 2009;López-Vázquez et al, 2012;Maltrana et al, 2004;Vélez and Rosso-Suárez, 2012;Yánez-García et al, 2003). In the present study, it was observed that 24% of clinical samples that were positive for fungal infection/colonization involved the maxillary sinus.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations